2015
DOI: 10.1515/bhk-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, food intake and exercise: Relationship with ghrelin

Abstract: SummaryObesity, a disorder of body composition, is defined by a relative or absolute excess of body fat. In general adult population, obesity has been associated with a diverse array of adverse health outcomes, including major causes of death such as cancer, diabetes, cardiovascular disease, as well as functional impairment from problems such as osteoarthritis and sleep apnea. Ghrelin is a newly discovered peptide hormone which plays an important role in obesity. It is a powerful, endogenous orexigenic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
(88 reference statements)
0
3
0
2
Order By: Relevance
“… [1] Thomas et al, 1989 ; Dietrich and McDaniel, 2004 ; Querido and Sheel, 2007 ; Gomes da Silva et al, 2010 ; Ferreira-Vieira et al, 2014 ; [2] Young, 2007 ; Korb et al, 2010 ; Fuss et al, 2015 ; [3] Martinsen, 1990 ; Scully et al, 1998 ; Craft and Perna, 2004 ; De Moor et al, 2006 ; Knapen et al, 2009 ; Carek et al, 2011 ; Vatansever-Ozen et al, 2011 ; DeBoer et al, 2012 ; Haasova et al, 2013 ; Mammen and Faulkner, 2013 ; de Souza Moura et al, 2015 ; Tiryaki-Sonmez et al, 2015 ; Weinberg and Gould, 2015 ; Meyer et al, 2016a , b ; [4] Marsh and Sonstroem, 1995 ; Fox, 2000 ; Berger and Motl, 2001 ; Landers and Arent, 2001 ; Urso and Clarkson, 2003 ; Craft, 2005 ; Penedo and Dahn, 2005 ; Raedeke, 2007 ; Stessman et al, 2009 ; Bartlett et al, 2011 ; Biddle et al, 2011 ; Rodgers et al, 2014 ; Zamani Sani et al, 2016 . …”
Section: Physical Exercise and Wellbeingunclassified
See 2 more Smart Citations
“… [1] Thomas et al, 1989 ; Dietrich and McDaniel, 2004 ; Querido and Sheel, 2007 ; Gomes da Silva et al, 2010 ; Ferreira-Vieira et al, 2014 ; [2] Young, 2007 ; Korb et al, 2010 ; Fuss et al, 2015 ; [3] Martinsen, 1990 ; Scully et al, 1998 ; Craft and Perna, 2004 ; De Moor et al, 2006 ; Knapen et al, 2009 ; Carek et al, 2011 ; Vatansever-Ozen et al, 2011 ; DeBoer et al, 2012 ; Haasova et al, 2013 ; Mammen and Faulkner, 2013 ; de Souza Moura et al, 2015 ; Tiryaki-Sonmez et al, 2015 ; Weinberg and Gould, 2015 ; Meyer et al, 2016a , b ; [4] Marsh and Sonstroem, 1995 ; Fox, 2000 ; Berger and Motl, 2001 ; Landers and Arent, 2001 ; Urso and Clarkson, 2003 ; Craft, 2005 ; Penedo and Dahn, 2005 ; Raedeke, 2007 ; Stessman et al, 2009 ; Bartlett et al, 2011 ; Biddle et al, 2011 ; Rodgers et al, 2014 ; Zamani Sani et al, 2016 . …”
Section: Physical Exercise and Wellbeingunclassified
“… [3] Martinsen, 1990 ; Scully et al, 1998 ; Craft and Perna, 2004 ; De Moor et al, 2006 ; Knapen et al, 2009 ; Carek et al, 2011 ; Vatansever-Ozen et al, 2011 ; DeBoer et al, 2012 ; Haasova et al, 2013 ; Mammen and Faulkner, 2013 ; de Souza Moura et al, 2015 ; Tiryaki-Sonmez et al, 2015 ; Weinberg and Gould, 2015 ; Meyer et al, 2016a , b ; …”
Section: Physical Exercise and Wellbeingunclassified
See 1 more Smart Citation
“…It is assumed that hormones regulating appetite, such as ghrelin, play a role in regulating calorie intake [38]. Studies conducted on obese and healthy individuals showed that ghrelin levels increased with weight loss after exercise and food restriction [40]. One of the consequences of physical activity is the increase in calorie expenditure that generates signals for ghrelin producing cells in the stomach, and these signals affect appetite regulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to existing data low physical activity and poor diet also contribute to the occurrence of chronic inflammation [ 6 ]. The link between physical inactivity and an increased risk of diseases associated with long-term inflammation has been well documented [ 7 , 8 ]. It is assumed that lack of physical activity promotes inflammation as it causes the body to store more fat, especially visceral fat [ 9 ].…”
Section: Introductionmentioning
confidence: 99%